Program Pengembangan Peternakan Itik Di Kabupaten Hulu Sungai Utara - Ahmad Zaky Maulana; Yudhi Putryanda (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2018)
The poultry sector in Hulu Sungai Utara district depends on the type of livestock development, including swamp buffalo farms, chicken farms and alabio duck farms which are also the superior products of North Hulu Sungai Regency. Duck farming can be an opportunity in accelerating development and regional economic growth. Therefore the management and utilization policy of this sector must be strengthened through policies, implementation of policies and innovative application techniques. This paper aims to describe the climate of innovation that must be achieved in the effort to develop duck farms in the Hulu Sungai Utara district. This paper uses a qualitative approach in describing various problems that are the problem of sector development innovation. The popularity of duck from upstream to culinary products can be a basic opportunity for duck development with a touch of innovation that can be applied to local government programs and policies. Development innovation is new programs that have never been implemented or modification of existing programs by incorporating elements of research in them to be able to meet the criteria of innovation policies in shaping an innovative business climate. In carrying out the effort to develop duck farming in Hulu Sungai Utara district, several things must be made to offer the local government programs, among others : 1) Strengthening duck database, 2) capacity building program, 3) ppl performance improvement program and strengthening animal husbandry institutions, 4) Procurement / system and institutional renewal, 5) Strengthening farm land status, 6) Livestock Infrastructure Development and Development, 7) Aid for duck processing technology with zero waste production method, 8) Expansion of cooperation between regional development agencies, 9) Removing various policies that hamper sustainability, 10) Strengthening Business Partnerships, 11) Strengthening MSMEs, 12) Mapping and collecting local innovators and involving them in diffusion of innovation, 13) Development of duck-based entrepreneurial institutions , 14) Construction of packaging houses with educated and trained personnel, 15) Training of standard certification SOPs and halal labels for duck-based entrepreneurs. Abstrak Sektor peternakan di Kabupaten Hulu Sungai Utara bergantu ng pada jenis pengembangan ternak antara lain peternakan kerbau rawa, peternakan ayam dan peternakan itik alabio yang juga merupakan produk unggulan Kabupaten Hulu Sungai Utara. Sektor peternakan itik dapat menjadi peluang dalam percepatan pembangunan dan pertumbuhan ekonomi daerah.Oleh karena itu kebijakan pengelolaan dan pemanfaatan sektor ini harus dikuatkan melalui kebijakan, implementasi kebijakan dan teknik penerapan yang inovatif. Tulisan ini bertujuan untuk mendeskripsikan iklim inovasi y ang harus dicapai dalam upaya pengembangan peternakan itik di Kabupaten Hulu Sungai Utara. Tulisan ini menggunakan pendekatan kualitatif dalam mendeskripsikan berbagai persoalan yang menjadi permasalahan inovasi pengembangan sektor. Popularitas ternak itik mulai dari hulu hingga produk kuliner dapat menjadi peluang dasar pengembangan itik dengan adanya sentuhan inovasi yang dapat diterapkan pada program dan kebijakan pemerintah daerah. Inovasi pengembanganmerupakan program program baru yang bel um pernah dilaksanakan mapun modifikasi program yang sudah ada dengan memasukkan unsur riset di dalamnya agar mampu memenuhi kriteria kebijakan inovasi dalam membentuk iklim usaha yang inovatif. Dalam melaksanakan upaya pengembangan usaha peternakan itik di kabupaten Hulu Sungai Utara maka beberapa hal yang harus menjadikan program pemerintah daerah yang ditawarkan antara lain : Penguatan basis data peternakan itik, 2) Program peningkatan kapasistas sdm, 3) Program peningkata n kinerja ppl dan penguatan kelembagaan peternakan, 4) Pengadaan/pembaharuan Sistem dan Kelembagaan, 5) Penguatan Status Lahan peternakan, 6) Pembangunan dan Pengembangan Infrastruktur Peternakan, 7) Bantuan teknologi pengolahan itik dengan metode zero waste production 8) Perluasan kerjasama antar lembaga kelitbangan daerah, 9) Menghapus berbagai kebijakan yang menghambat keberlangsungan kelitbangan, 10) Penguatan Kemitraan Bisnis, 11) Penguatan UMKM, 12) Pemetaan dan pendataan innovator lo kal dan melibatkannya dalam difusi inovasi, 13) Pengembangan kelembagaan wirausaha berbasis itik, 14) Pembangunan rumah kemasan dengan personil yangterdidik dan terlatih, 15) Pelatihan SOP sertifikasi standar dan label halal bagi para wirausaha berbasis itik.